Opportunity or threat? The views of bankers towards crowdfunding - Laffey, Des; Durkin, Mark; Cummins, Darryl; Gandy, Anthony (Senate Hall, 2021)
Crowdfunding has emerged as an innovative source of finance for start-ups and small and medium sized enterprises. This paper considers the views of the most important source of small business finance, retail banks, on crowdfunding. The paper identifies four key themes which emerged from interviews with respondents with experience as senior bank employees in the UK and Ireland. Firstly, firms which sought crowdfunded finance were seen as being too risky for traditional bank lending. Second, the respondents did not see crowdfunding as a threat to the business banking sector. Third, the respondents felt that banks provided a wide range of advice and services which protected them from innovations such as crowdfunding. Finally, crowdfunding was seen as a potential complementary product that could be suggested to firms as it would fund risky propositions that the banks would not support. The paper then offers some practical implications before it concludes.
Keywords: crowdfunding